A common gesture with a rare but potentially severe complication: Re-expansion pulmonary edema following chest tube drainage. (2019) - Kepka, S.; Lemaitre, L.; Marx, T.; Bilbault, P.; Desmettre, T.
Abstract: Background: Primary Spontaneous Pneumothorax (PSP) is usually considered as a benign pathology occurring in young people. In about half of cases, observation only is purposed. In case of intervention, chest tube drainage remains the preponderant strategy even if no studies conclude about superiority of drainage or aspiration. Re-expansion pulmonary edema (REPE) is a rare but potentially severe complication of chest tube drainage. Risk factors are not well identified, but REPE is more frequent for patients with diabetes, younger than 40 years, with large pneumothorax, lung collapse more than one week and fast re-expansion. Case report: We report a case of a 19-year old male presenting to the Emergency Department with a first episode of PSP. He was treated by chest tube drainage with immediate suction. He developed a REPE 3 hours after chest tube drainage with suction. Conservative management and oxygen therapy led to withdrawing the chest tube 9 days later. Conclusion: For the initial management of PSP, prevention of this complication is essential. In case of risk factors, prevention consist of absence of immediate suction after chest tube drainage and suction should be reserved in case of failure of initial treatment after 24 hours. Even if chest tube drainage is a common gesture, clinical presentation of REPE must alert physicians taking care of these patients.